Mecanismos de resistencia a metales pesados en Erica andevalensis - Márquez-García, B. (Ecosistemas, 2009)
Márquez-García, B. (2009). Mecanismos de resistencia a metales pesados en Erica andevalensis. Ecosistemas 18(3):27-29.